Pengaruh Online Customer Review Dan Promosi Penjualan Terhadap Keputusan Pembelian Produk Di E-commerce Shopee - Irawan, Marko; Utami Puji Lestari (Jurnal Manajemen dan Pemasaran, 2024)
The e-commerce phenomenon is changing consumers' views on shopping. E-commerce in the fast-growing digital era has changed consumers' perspective on purchasing. With a wide selection of products from fashion, food, electronics, and other daily necessities, Shopee is one of the leading e-commerce platforms in Indonesia. The type of research used is quantitative. This study involved a sample of 50 Shopee users as respondents. Primary data was obtained through the use of questionnaires, while secondary data from references such as journals, books, and other sources of information were used to support the primary data. This study used multiple linear regression analysis to examine the relationship between the independent variables (customer reviews and sales promotion) and the dependent variable (purchase decision). The analysis was conducted using SPSS version 26 software by conducting validity, reliability, and other tests. OCR and sales promotion on the decision to make a purchase have no partial effect. This reinforces that Online Customer Review does not always form a strong perception to increase buyer intention and intention in a purchasing decision, nor does sales promotion always increase buyer interest and intention in purchasing decisions.